It is given that f : R → R is defined by f(x) = x2 – 3x + 2.
f(f(x)) = f (x2 – 3x + 2)
= (x2 – 3x + 2)2 - 3(x2 – 3x + 2) + 2
= x4 + 9x2 + 4 – 6x3 -12x + 4x2 – 3x2 + 9x – 6 + 2
= x4 - 6x3 + 10x2 - 3x
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation